Clinical and genetic diagnosis of familial hypercholesterolaemia in patients undergoing coronary angiography: the Ludwigshafen Risk and Cardiovascular Health Study - Molnar, Stefan; Scharnagl, Hubert; Delgado Gonzales de Kleber, Graciela; Krämer, Bernhard; Laufs, Ulrich; März, Winfried; Kleber, Marcus E.; Katzmann, Julius Ludwig (European heart journal - quality of care and clinical outcomes, 2024)
To investigate the prevalence of familial hypercholesterolaemia (FH) and compare the performance of clinical criteria and genetic testing in patients undergoing coronary angiography.The prevalence of FH was determined with the Dutch Lipid Clinical Network (DLCN), US ‘Make Early Diagnosis to Prevent Early Death’ (US-MEDPED), Simon Broome (SB) criteria, the ‘familial hypercholesterolaemia case ascertainment tool’ (FAMCAT), and a clinical algorithm. Genetic screening was conducted with a custom array from Affymetrix (CARRENAL array) harbouring 944 FH mutations.The study cohort consisted of 3267 patients [78.6% with coronary artery disease (CAD)]. FH was diagnosed in 2.8%, 2.2%, 3.9%, and 7.9% using the DLCN, US-MEDPED, SB criteria, and the FAMCAT. The clinical algorithm identified the same patients as the SB criteria. Pathogenic FH mutations were found in 1.2% (1.2% in patients with CAD, 1.0% in patients without CAD). FH was more frequently diagnosed in younger patients. With genetic testing as reference, the clinical criteria achieved areas under the ROC curve [area under the curves (AUCs)] in the range of 0.56-0.68. Using only low-density lipoprotein cholesterol (LDL-C) corrected for statin intake, an AUC of 0.68 was achieved.FH is up to four-fold more prevalent in patients undergoing coronary angiography than in contemporary cohorts representing the general population. Different clinical criteria yield substantially different diagnosis rates, overestimating the prevalence of FH compared with genetic testing. LDL-C testing alone may be sufficient to raise the suspicion of FH, which then needs to be corroborated by genetic testing.In this study, we investigated the frequency of familial hypercholesterolaemia—a common genetic condition leading to markedly elevated low-density lipoprotein (LDL) cholesterol and increased risk of atherosclerosis—in 3267 patients undergoing coronary angiography according to commonly used diagnostic scoring systems and genetic testing. Genetically confirmed familial hypercholesterolaemia was four-fold more prevalent in patients undergoing coronary angiography compared with contemporary cohorts representing the general population, and was more often diagnosed in younger patients.Compared with genetic testing—the gold standard to diagnose familial hypercholesterolaemia—the diagnostic scoring systems only modestly discriminated between healthy individuals and those with familial hypercholesterolaemia. Importantly, LDL cholesterol testing alone provided equivalent diagnostic information compared with any of the scores.
Corrected and typeset: 17 January 2024
Gesehen am 14.03.2024